2014
DOI: 10.1016/j.neuroimage.2013.04.072
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared spectroscopy versus magnetic resonance imaging to study brain perfusion in newborns with hypoxic–ischemic encephalopathy treated with hypothermia

Abstract: Background The measurement of brain perfusion may provide valuable information for assessment and treatment of newborns with hypoxic-ischemic encephalopathy (HIE). While arterial spin labeled perfusion (ASL) magnetic resonance imaging (MRI) provides noninvasive and direct measurements of regional cerebral blood flow (CBF) values, it is logistically challenging to obtain. Near-infrared spectroscopy (NIRS) might be an alternative, as it permits noninvasive and continuous monitoring of cerebral hemodynamics and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
68
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 56 publications
(84 reference statements)
1
68
0
7
Order By: Relevance
“…Developmental and HIE-related changes in cerebral hemodynamics between 24 and 72 h after birth are also major confounders, considering the variation in HIE severity among patients. Indeed, Wintermark et al reported a tendency for a greater decrease in both oxygen supply and demand or utilization over time in severely asphyxiated neonates compared with moderately asphyxiated neonates during HT [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Developmental and HIE-related changes in cerebral hemodynamics between 24 and 72 h after birth are also major confounders, considering the variation in HIE severity among patients. Indeed, Wintermark et al reported a tendency for a greater decrease in both oxygen supply and demand or utilization over time in severely asphyxiated neonates compared with moderately asphyxiated neonates during HT [14].…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4]14,15].Toet et al and Ancona et al reported increased cerebral oxygenation (increased Table 2A Mean CBV and ScO 2 values (± SD) at 6, 24, 48, and 72 h after birth according to clinical outcome.…”
mentioning
confidence: 96%
“…We can, however, not exclude pathological conditions associated with differences in CBF, such as hypoxic-ischemic encephalopathy and PAIS, from influencing the results. 1,39,40 The largest bias (i.e. rScO 2-NIRS À SO 2-T2-BIOS ¼ À20%) was shown on the affected side in the infant with unilateral ventricular dilatation.…”
Section: Discussionmentioning
confidence: 97%
“…The most accepted are positron emission tomography (PET), 31,32 magnetic resonance imaging (MRI) (including functional MRI), 33À36 Doppler ultrasound and near-infrared spectroscopy (NIRS). 37,38 MRI provides high-resolution structural images but needs much time for data acquisition and processing and does not supply with information about blood°ow parameters. fMRI and PET use radioactive contrast agents to retrieve the data concerning with blood°ow and blood volume in the sample and have relatively low spatial and temporal resolution.…”
Section: à11mentioning
confidence: 99%